Muzzle characteristics in the dermatoglyphics of muzzle of different breeds of cattle - MISHRA, SHARAD; TOMER, O S; KALM, E (The Indian Journal of Animal Sciences, 2013)
Dermatoglyphics of muzzle in 6 breeds of cattle, viz. Tharparkar, SahiwaJ, Karan Swiss, Karan Fries, Red and White, and Black and White, were studied to find out the; breed differences in terms of muzzle characteristics. The differences in beads at base sector and at middle sector among/Tharparkar, Sahiwal and Karan Swiss were nonsignificant. The characteristics were significantly (P